ANALISIS KINERJA KEUANGAN PADA PT. ASTRA INTERNATIONAL, TBK - Thessalonica S.F. Supit; Welly .A. Areros; Johny .R.E. Tampi (Universitas Sam Ratulangi, 2016)
Abstract. This study aimed to analyze the financial performance of PT. Astra International Tbk based Ratios Liquidity, Solvency and Profitability